2015
DOI: 10.1680/macr.14.00114
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour of reinforced concrete beams with non-bonded flexural reinforcement

Abstract: The work presented concerns an investigation of the effect of bond between concrete and longitudinal reinforcement on the behaviour of reinforced concrete beams, without transverse reinforcement, subjected to transverse loading combined with an axial force in selected cases. The results showed that the development of bond anywhere within the shear span inevitably leads to inclined cracking, which is the cause of ‘shear' failure. Similarly, eliminating bond throughout the beam's span was also found not to safeg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 9 publications
1
6
1
Order By: Relevance
“…Apart from possible enhancement in load capacity, Ikeda and Uji (1980) were amongst the first to demonstrate that bond deterioration has also the potential to alter the mode of failure of shear critical beams. This was confirmed more recently by Kotsovos et al (2015) who found that by removing the bond between concrete and reinforcement, premature shear failure in concrete beam can possibly be either delayed or prevented.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Apart from possible enhancement in load capacity, Ikeda and Uji (1980) were amongst the first to demonstrate that bond deterioration has also the potential to alter the mode of failure of shear critical beams. This was confirmed more recently by Kotsovos et al (2015) who found that by removing the bond between concrete and reinforcement, premature shear failure in concrete beam can possibly be either delayed or prevented.…”
Section: Introductionmentioning
confidence: 54%
“…Figure 2a displays the longitudinal profile and crosssectional details of one of the two series of beams tested by Kotsovos et al (2015). All beams were of rectangular cross section with the same width (150 mm) and overall depth (300 mm).…”
Section: Beam Geometry and Finite Element Meshesmentioning
confidence: 99%
See 1 more Smart Citation
“…Muttoni and Schwartz [62] and later Muttoni and Fernández Ruiz [6] suggested that the alteration of the cracking pattern could prevent or delay the development of cracks crossing the diagonal struts close to the supports, leading to an increase in shear resistance. This was based on studies where the alteration of the cracking pattern was due to the debonding the longitudinal reinforcement [44,57,63], an effect later replicated by others [64][65][66]. This alteration of the internal resisting mechanism in the concrete can be interpreted through the mechanism of shear resistance presented earlier in Eq.…”
Section: Shear Resistance Of Reinforced Concrete Without Transverse R...mentioning
confidence: 86%
“…Based on the above studies and early work by Muttoni and Thürlimann [80], it was pointed out that the enhancement in shear behaviour was related to the alteration of the cracking pattern and the beneficial effect of preventing or delaying the development of cracks crossing the diagonal struts close to the support [3,81]. Kotsovos et al [82] investigated the effects of a reduction in steel-to-concrete bond of longitudinal bars on beams with an effective depth of 270 mm and 170 mm, corresponding to 𝑎∕𝑑 values of 2.9 and 4.6, respectively. By progressively varying the unbonded length, they obtained the greatest uplift when the unbonded length extended from the support to a distance 2.5 times the effective depth.…”
Section: Introductionmentioning
confidence: 99%